Effect of ethanolic extract of Zingiber officinale on growth performance and mucosal immune responses in rainbow trout (Oncorhynchus mykiss). (15th July 2016) - Shaluei, F.; Nematollahi, A.; Naderi‐Farsani, H.R.; Rahimi, R.; Kaboutari Katadj, J.
Abstract: This study was conducted to examine the effect of ethanolic ginger ( Zingiber officinale ) extract on growth performance and some skin mucus immune parameters in rainbow trout ( Oncorhynchus mykiss ). A total of 600 rainbow trout fingerling (10.07 ± 0.21 g) were randomly assigned to four groups in triplicate and fed for 45 days with 1, 2.5 and 5 g kg −1 of ginger extract and with unsupplemented basal diet as the control. The total protein content and lysozyme, alkaline phosphatase and protease activities of skin mucus were investigated following 15, 30 and 45 days of feeding. Results showed that administration of 2.5 and 5 g kg −1 of ethanolic ginger extract for 45 days improved weight gain, feed utilization efficiency and feed conversion ratio of O. mykiss ( P  < 0.05). Significantly higher ( P  < 0.05) skin mucus lysozyme, alkaline phosphatase and protease activity and protein level were observed in the 2.5 and 5 g kg −1 ginger extract groups on the 30th and 45th day compared to the controls. The findings suggest that ethanolic extract of ginger enhances growth performance and skin mucus immune parameters of rainbow trout.